Bahasa sebagai Cerminan Identitas Personal di Era Digital - Nazwa Dewi Tianda; Delfi Wulandari; Lidwina Roulina Turnip; Safana Nur Rizky; Ahmad Rifki Alparwis; Amelisa Siahaan; Devi Ruth Chayana Saragih; Madeline Samaeri Harefah (International Forum of Researchers and Lecturers, 2024)
Language in the digital era functions not only as a communication tool but also as a reflection of personal and collective identity. Language use on digital platforms, such as social media, reflects self-expression, image building, and cultural affiliation. However, globalization and the dominance of foreign languages, especially English, pose challenges to preserving local identity. This study employs a qualitative approach through interviews and document analysis to explore how language shapes personal identity in the digital era. The findings indicate that language in digital spaces allows individuals to express creativity while facing social pressures to construct specific images. Nonetheless, phenomena such as code-switching and slang usage highlight the influence of global culture. To maintain a balance between global adaptation and local cultural preservation, collaboration among individuals, communities, and governments is needed through education, cultural campaigns, and technology. With this approach, language can become a tool for fostering cultural solidarity and preserving diversity in an increasingly connected world.